Dimensi Math Anxiety (Kognitif, Sikap, Somatik) terhadap Kemampuan Pemahaman Konsep Matematis pada Materi SPLTV - Putri, Citra Nurani; Hakim, Dori Lukman (PHI: Jurnal Pendidikan Matematika, 2022)
This article discusses the relationship between math anxiety in each dimension to students' mathematical concept comprehension ability in SPLTV material. The subjects of this study were 38 students of class X science 1 at SMAN 2 Telukjambe Timur. This research uses qualitative descriptive method. The instrument in this study is in the form of a 6-question description test instrument containing indicators of understanding concepts and 30 items of math anxiety questionnaires. The analytical techniques used are data reduction, presenting data, and drawing conclusions. And from the results of the study, the average score of class X science 1 students of SMAN 2 Telukjambe Timur was obtained in the math anxiety questionnaire on the cognitive, attic, and somatic dimensions successively of 23.41; 27.25; and 11.56pm. And the average value of mathematical concept comprehension ability is 49.89. It was also found that math anxiety has an influence on students' ability to understand mathematical concepts, with the opposite direction of influence.